Cetacean sightings and acoustic detections during a seismic survey off Nicaragua and Costa Rica, November-December 2004 - Holst, Meike (2017)
Although the wider Eastern Tropical Pacific has been systematically surveyed during summer/fall, relatively little effort has focused on shelf and slope waters of Nicaragua and Costa Rica. Such data are useful for establishing baseline information and assessing potential changes in cetacean occurrence and distribution relative to natural (e.g., El Niño-Southern Oscillation, climate change) and anthropogenic factors. A visual-acoustic survey for cetaceans occurred as part of a monitoring and mitigation program during an academic geophysical seismic study off Nicaragua and Costa Rica, during November-December 2004. Approximately 2 067 cetaceans representing at least seven species were seen in 75 groups during 373 h (3 416 km) of daytime observations from the seismic research vessel (R/V) Maurice Ewing. The humpback whale (Megaptera novaeangliae) and the pantropical spotted dolphin (Stenella attenuata) were the most frequently sighted species (30 % of all groups sighted); both were seen in shelf waters < 100 m deep and in slope waters. The bottlenose dolphin (Tursiops truncatus; 10 % of sightings) was the third most frequently sighted species and was only seen in water > 100 m deep. In addition, sightings were made of spinner dolphins (S. longirostris), short-beaked common dolphins (Delphinus delphis), Risso’s dolphins (Grampus griseus), short-finned pilot whales (Globicephala macrorhynchus), and unidentified dolphins and whales. Unconfirmed sightings of a minke whale (Balaenoptera acutorostrata) and a pod of false killer whales (Pseudorca crassidens) were also recorded. An additional six groups of dolphins (50 % confirmed to species, all pantropical spotted dolphins) were made during 187 h (1 549 km) of observation effort during darkness, two of which were detected within 30 m of the vessel bow using a night vision device. A total of 217 cetacean detections occurred during 633 h of passive acoustic monitoring. A small concentration of 12 humpback whales was seen in eight groups, and two humpbacks were recorded singing in the Gulf of Fonseca on 9 December 2004. To our knowledge, such concentrations of humpback whales, particularly singing humpbacks, have not been previously reported in this specific area. In addition, a humpback mother-calf pair, likely from the Northern Hemisphere population, was seen off Northern Costa Rica on 25 November 2004. Although cetacean sighting rates were significantly different during seismic and non-seismic periods even when corrected for differential detection probability related to sea conditions, our survey results do provide information to address previous data gaps on cetacean occurrence in shelf and slope waters off the Pacific coast of Central America during late fall.